Lehrkraft-Eltern-Interaktionen am Elternsprechtag Eine gesprächs- und gattungsanalytische Untersuchung - Wegner, Lars (Empirische Linguistik / Empirical Linguistics, 2016)
Empirical approaches based on qualitative or quantitative methods of corpus linguistics have become a central paradigm within linguistics. The series takes account of this fact and provides a platform for approaches within synchronous linguistics as well as interdisciplinary works with a linguistic focus which devise new ways of working empirically and develop new data-based methods and theoretical models for empirical linguistic analyses.